2024
DOI: 10.3389/fvets.2024.1383801
|View full text |Cite
|
Sign up to set email alerts
|

A study on the treatment effects of Crataegus pinnatifida polysaccharide on non-alcoholic fatty liver in mice by modulating gut microbiota

Ping Hao,
Xiaonan Yang,
Wen Yin
et al.

Abstract: The objective of this study was to investigate the protective effect of Crataegus pinnatifida polysaccharide (CPP) on non-alcoholic fatty liver disease (NAFLD) induced by a high-fat diet (HFD) in mice. The findings demonstrated that CPP improved free fatty acid (FFA)-induced lipid accumulation in HepG2 cells and effectively reduced liver steatosis and epididymal fat weight in NAFLD mice, as well as decreased serum levels of TG, TC, AST, ALT, and LDL-C. Furthermore, CPP exhibited inhibitory effects on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…WE is known for its sedative, diuretic, and spleen-boosting properties [ 26 ]. Recent studies have demonstrated that CP extracts, including polysaccharides, corosolic acid, hyperoside, and maslinic acid, protect against HFD-induced obesity and nonalcoholic fatty liver disease [ 27 , 28 , 29 , 30 ]. In addition, WE polysaccharides and triterpenoids have also been reported to reduce lipid accumulation and ameliorate hepatic steatosis in obese mice [ 18 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…WE is known for its sedative, diuretic, and spleen-boosting properties [ 26 ]. Recent studies have demonstrated that CP extracts, including polysaccharides, corosolic acid, hyperoside, and maslinic acid, protect against HFD-induced obesity and nonalcoholic fatty liver disease [ 27 , 28 , 29 , 30 ]. In addition, WE polysaccharides and triterpenoids have also been reported to reduce lipid accumulation and ameliorate hepatic steatosis in obese mice [ 18 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%